Comparison of different serological methods to detect antibodies specific to Neospora caninum in bovine and canine sera. (January 2014) - Ghalmi, Farida; China, Bernard; Jenkins, Mark; Azzag, Naouelle; Losson, Bertand
Neospora caninum is an apicomplexan parasite responsible for paresis in dogs and abortion in cattle worldwide. Dogs serve as a definitive host, while cattle serve as intermediate host. Many different methods have been developed to detect specific antibodies present in cattle and dog serum. In the present study, the dense granule protein NcGRA6 was incorporated in a latex beads agglutination test (LAT), and compared to other serological methods, including enzyme-linked immunosorbent assay, the direct agglutination test, the immunoblot, and the indirect fluorescent antibody test (IFAT). Using the IFAT as the reference method, 100 sera isolated from Algerian cattle and 100 sera isolated from Algerian dogs, both possibly infected with N. caninum, were used to evaluate the LAT. The sensitivity, specificity, and kappa index were calculated for each host species and assay. For dog sera, the sensitivity and the specificity of the LAT was 76% and 100%, respectively. The McNemar test showed that the LAT was not significantly different from IFAT ( P > 0.05). For cattle sera, the sensitivity and the specificity of the LAT were 60% and 100%, respectively. The McNemar test indicated that the LAT was significantly different from IFAT ( P < 0.01) and that the LAT was only positive for cattle sera with titers of 1:800 or greater, indicating that LAT can be used for cattle in a clinical context. As well, the LAT has the advantage of being easy and rapid to perform compared to the other assays.